MENDIDIK KARAKTER ANAK MELALUI PENDIDIKAN AGAMA DI SEKOLAH DASAR - Oswaldus Bule (Unika Santu Paulus Ruteng, 2020)
Religious Education and Character Education are two important fields that function to shape the students. As important activities, both can offer solutions to problems faced by students. Both can also be the key to opening the deadlock for the actualization of their potential. This paper discusses efforts to educate the character of children through Catholic Religious Education in Elementary School. The discussion is based on the awareness that with good character children will grow and develop optimally. Children will be able to contribute to human civilization and the welfare of society. This paper is done by applying a literature study. The author studies literature about Catholic religious education in elementary schools and about character education. Specifically, the author examines the formulation of core competencies and basic competencies of Catholic Religious Education. The core competencies are divided into four aspects, namely the core competencies of spiritual attitudes, social attitudes, knowledge, and skills. The formulation of core competencies contains values ​​which according to the author are the same and in line with the values ​​of Character Education. These values ​​include religious values, honesty, courtesy, fairness, responsibility, respect, confidence, love of truth, logical, critical, creative, innovative, love of nation. These values ​​can be classified in moral knowledge, moral feelings, and moral conduct. Can also be grouped in the value of a relationship with God, with oneself, with others, and with nature. Similarly, it can be divided into individual, social, and moral values. The author concludes that Religious Education has a major contribution to the formation of children's character